Sobre la fortuna de Boccaccio en la tradición peninsular. Las primeras traducciones catalanas y la incorporación de la misoginia en Cataluña. - DE LLOBET, LOLA ESTEVA (Scripta, 2013)
The Catalan translation of II Corbaccio made by the merchant Narcís Franch (1948) initiates a double stream of though in the Spanish peninsula about misogyny and feminism. His arguments became part of the misogyny though defended by Arciprestre de Talavera, Bernat Metge, Jaume Roig, Francesc Eiximenis and Pere Torrelles. Nevertheless, this trend of though about disgrace and invective against women also had its detractors, which originated the socalled «querelle des femmes» in defense of their values. Men and women like Christine de Pizan, Teresa de Cartagena, Isabel, Enrique de Villena and Rodríguez del Padrón attacked the systematic condemnation of women, inspired by the Claris mulieribus of Boccaccio. Based on the arguments pro and against female of La Fiammetta and Il Corbaccio, this article will reviews other texts and misogynous arguments of the tradition, with the purpose of concluding my theory about the «querelle des femmes» in Catalonia and Castile.